MODAL OPERATORS IN MODERN ENGLISH AND DUTCH - Botsman, A.V. (Studia Philologica, 2016)
The article deals with the peculiarities of modal verbs and periphrastic constructions in modern English and Dutch. The status of these verb groups was determined, and the most recognative features of them were singled out and described. The semantic aspects of these groups were observed in close comparison of English and Dutch. Distinct criteria for the classif cation of modals, auxiliaries and periphrastics were set out. Comparison of similarity and dif erence was based on the belonging of English and Dutch to the West subgroup of the Germanic languages.